Polystyrene Thin Films Nanostructuring by UV Femtosecond Laser Beam: From One Spot to Large Surface - Olga Shavdina; Hervé Rabat; Marylène Vayer; Agnès Petit; Christophe Sinturel; Nadjib Semmar (Nanomaterials, 2021)
In this work, direct irradiation by a Ti:Sapphire (100 fs) femtosecond laser beam at third harmonic (266 nm), with a moderate repetition rate (50 and 1000 Hz), was used to create regular periodic nanostructures upon polystyrene (PS) thin films. Typical Low Spatial Frequency LIPSSs (LSFLs) were obtained for 50 Hz, as well as for 1 kHz, in cases of one spot zone, and also using a line scanning irradiation. Laser beam fluence, repetition rate, number of pulses (or irradiation time), and scan velocity were optimized to lead to the formation of various periodic nanostructures. It was found that the surface morphology of PS strongly depends on the accumulation of a high number of pulses (103 to 107 pulses) at low energy (1 to 20 µJ/pulse). Additionally, heating the substrate from room temperature up to 97 °C during the laser irradiation modified the ripples’ morphology, particularly their amplitude enhancement from 12 nm (RT) to 20 nm. Scanning electron microscopy and atomic force microscopy were used to image the morphological features of the surface structures. Laser-beam scanning at a chosen speed allowed for the generation of well-resolved ripples on the polymer film and homogeneity over a large area.